Frailty and Risk of Dementia in Mild Cognitive Impairment Subtypes. Issue 6 (21st March 2021) - Ward, David D.; Wallace, Lindsay M. K.; Rockwood, Kenneth
Abstract : Risk factors for developing dementia from mild cognitive impairment (MCI) probably differ between MCI subtypes. We investigated how frailty relates to dementia risk in amnestic MCI (a‐MCI; n = 2, 799) and non‐amnestic MCI (na‐MCI; n = 629) in the National Alzheimer's Coordinating Center database. Although higher frailty increased dementia risk for people with either a‐MCI or na‐MCI, the larger risk was in na‐MCI (interaction hazard ratio = 1.35 [95% confidence interval = 1.15–1.59], p < 0.001). Even after the onset of clinically significant cognitive impairment, poor general health, quantified by a high degree of frailty, is a significant risk for dementia. ANN NEUROL 2021;89:1221–1225